Error analysis of scientific papers written by non‐native speakers of English - Marina, Valerija; Snuviškiene, Genovaite (Transport, 2005)
The paper presents linguistic error analysis of articles written by non‐native speakers of English which were published in the journal ‘Transport’ in 2003–2004. The errors were identified, classified and analysed from various perspectives. The main causes of language misuse were also identified and explained within the framework of the theory of linguistic relativity and laws of interference of the native language of the learners. The analysis is aimed at building competence of technical writers in the English language used in scientific papers. The results obtained in the investigation allowed the authors to provide some recommendations to technical writers as to improving the proficiency in scientific English.First Published Online: 27 Oct 2010